Depressive Disorders Are Associated With Risk of Falls in People With Chronic Kidney Disease. (May 2022) - Kistler, Brandon M.; Khubchandani, Jagdish; Bennett, Paul; Wilund, Kenneth R.; Sosnoff, Jacob
OBJECTIVES: People with chronic kidney disease (CKD) are at increased risk for falls and fall-related injuries. Depressive disorders (DEP) are common in individuals with CKD and may increase the risk of falls and fall-related injuries. However, not much is known about the relationship between DEP and falls in people with CKD. The purpose of this study was to determine the influence of DEP on the relationship between CKD, falls, and fall-related injuries. METHOD: Using the Behavioral Risk Factor Surveillance System, we identified 16, 574 adults with CKD. Patients with CKD were stratified by history of self-reported DEP (SRDEP), and multivariate logistic regression was conducted to determine the odds for falls and fall-related injuries among those with and without SRDEP. RESULTS: In unadjusted regression analysis, falls (OR = 2.40, 95% CI = 2.08-2.76) and fall-related injuries (OR = 2.12, 95% CI = 1.72-2.59) were higher in individuals with CKD and history of SRDEP compared to those with CKD and no history of SRDEP. Adjustment for confounders had little effect on the relationship between a history of SRDEP and either falls (AOR = 1.87, 95% CI = 1.60-2.19) or fall-related injuries (AOR = 1.58, 95% CI = 1.26-1.97). CONCLUSIONS: People with CKD and DEP are at increased odds for falls and fall-related injuries even after adjustment for sociodemographic, lifestyle factors, and comorbidities. Prospective studies are warranted to further understand this relationship, but it may be prudent for clinicians, in particular nurses, to consider fall risk when treating DEP in patients with CKD.